Concerns Regarding Article: 10.4103/ni.ni_800_22: Normative Data of Montreal Cognitive Assessment (MoCA) in Tamil Speaking Adults - A P Porrselvi (Neurology India, 2025)
BACKGROUND: Cervical cancer is a leading cause of cancer-related deaths in women in low-and middle-income countries. Awareness plays a crucial role in early diagnosis and prevention. Among social media platforms, YouTube offers extensive health awareness content, including information on cervical cancer. However, the validity, reliability, and usefulness of this content are not known. This study aimed to evaluate the quality and validity of widely viewed Hindi YouTube videos on cervical cancer. METHODS: YouTube was searched using the term "cervical cancer-Hindi." The 50 most-viewed Hindi videos were manually coded and statistically analyzed. Reliability was assessed using the DISCERN scale, while quality, credibility and usefulness were evaluated using the Journal of the American Medical Association (JAMA) and Global Quality Score (GQS) tools. Two experienced public health researchers independently rated the videos, and their agreement correlation scores were calculated. Videos from professionals, news organizations, and individuals were compared. RESULTS: Among the 50 videos, 78% were uploaded by professionals ( N = 39), 14% by news organizations ( N = 7), and 8% by individuals ( N = 4). The DISCERN median 36.50 (31-42), GQS median 8.00 (6.00-10.00), and JAMA median 6.00 (4.00-8.00) were reported. Observers' agreement for JAMA, GQS, and DISCERN was statistically significant. However, no significant differences were observed between professionals, individuals, and news organizations, or between genders and content types. CONCLUSION: Valid, reliable, and good-quality cervical cancer videos are available on YouTube and widely viewed. However, as no creator type showed significantly better quality, more efforts by professionals and news organizations are needed to enhance video reliability and awareness outcomes.